Necessity for up-scaling resource mobilization for implementation of competency-based curriculum at basics education cycle - njati, ibuathu (African Journal of Science, Technology and Social Sciences, 2022)
School resources comprise necessary materials, both financial and human. A growth towards evidence-based allocation and utilization of school resources is affected by inadequate capacity of the school managers, ministry of education, parents and non-governmental organizations. Inadequate teaching and learning resources limit individual schools' strength to make judicial decisions on equitable trade-offs in education resource demand, supply and consumption. This work sought to identify the locally available resources for utility in competency-based- curriculum implementation, improve the available resources for enhancing teaching and learning, and analyze factors militating against effective mobilization and utilization of resources at the basic education level. Online surveys were used in collecting secondary data. Journals, internet, textbooks and research reports were sampled for data gathering through a stratified sampling technique. The findings showed that the rural-urban migration factors significantly affect trained teachers from arid areas by moving away from their local homes to towns in search of jobs. When learners fail to interact adequately with qualified teachers, the consequences are dire, resulting in learners' poor acquisition of competencies. It was ascertained that more than 70% of the teachers teaching at Kakuma Refugee Camp were not sensitive to learners' plights. This was due to their weak and inadequate education and training background coupled with poor teaching and learning resources. 60% of the tutors at Kakuma Refugee Camp were untrained in pedagogical and andragogical skills necessary for giving instructions in a competency-based curriculum. It was established that the cost of needed materials and training for improving CBC implementation was expensive. Therefore, action research could explore avenues for economies of scale by sharing materials and coordinating purchases between and among neighborhood schools. This is because the critical mass of activities under CBC such as arts, music and sports all create new opportunities for supply chains that present avenues for partnering with organizations that support basic education activities that has remained unexploited. In conclusion, the national and county government's department of pre-primary and basic education level should generate guidance on the use of alternative and low-cost materials for teaching to alleviate the persistent shortages of teaching resources. Key Words: resources, mobilization, utilization; competency-based-curriculum; enhancing teaching and learning,